Familial cancer: how to successfully recruit families for germline mutations studies? Multiple myeloma as an example - Blocka, Joanna; Durie, Brian G. M.; Huhn, Stefanie; Müller-Tidow, Carsten; Försti, Asta; Hemminki, Kari; Goldschmidt, Hartmut (Clinical lymphoma, myeloma & leukemia, 2019)
Introduction - Identification of germline mutations related to an increased cancer risk enables diagnostic, preventive, and therapeutic measures for individuals carrying the disease variant. However, recruitment of families for studies on these mutations can be challenging. Herein we present some of the obstacles that can arise during such studies. We suggest solutions for overcoming or avoiding these difficulties, enabling an efficient and ethically correct family recruitment. - Patients and Methods - We describe a study on germline mutations associated with familial risk of multiple myeloma using next-generation sequencing of the whole genome. To date, the study has recruited 54 participants/16 families from different centers in Germany. It was performed at the University Hospital of Heidelberg and German Cancer Research Center. - Results - We were confronted with ethical/psychological concerns of patients and family members, a large number of ineligible families, a profound time investment by the participants and the study team, incidental findings, and participants’ death. We present solutions to these difficulties such as: knowledge of and adherence to the laws protecting participants’ rights, an exact clarification of the inclusion and exclusion criteria, a clear division of tasks within members of the study team, a collaboration with general practitioners/oncologists and patients’ support groups, a detailed and understandable informed consent including information about incidental findings, and a choice of a representative in case of participant’s death. - Conclusion - A successful recruitment for studies on familial cancer is challenging, yet possible. It can be facilitated by applying the previously mentioned strategies.
Gesehen am 02.12.2019